The Impact of Couple HIV Testing and Counseling on Consistent Condom Use Among Pregnant Women and Their Male Partners: An Observational Study. (1st August 2017) - Rosenberg, Nora E.; Graybill, Lauren A.; Wesevich, Austin; McGrath, Nuala; Golin, Carol E.; Maman, Suzanne; Bhushan, Nivedita; Tsidya, Mercy; Chimndozi, Limbikani; Hoffman, Irving F.; Hosseinipour, Mina C.; Miller, William C.
Abstract : Background: In sub-Saharan Africa couple HIV testing and counseling (CHTC) has been associated with substantial increases in safe sex, especially when at least one partner is HIV infected. However, this relationship has not been characterized in an Option B+ context. Setting: The study was conducted at the antenatal clinic at Bwaila District Hospital in Lilongwe, Malawi in 2016 under an Option B+ program. Methods: Ninety heterosexual couples with an HIV-infected pregnant woman (female-positive couples) and 47 couples with an HIV-uninfected pregnant woman (female-negative couples) were enrolled in an observational study. Each couple member was assessed immediately before and 1 month after CHTC for safe sex (abstinence or consistent condom use in the last month). Generalized estimating equations were used to model change in safe sex before and after CHTC and to compare safe sex between female-positive and female-negative couples. Results: Mean age was 26 years among women and 32 years among men. Before CHTC, safe sex was comparable among female-positive couples (8%) and female-negative couples (2%) [risk ratio (RR): 3.7, 95% confidence interval (CI): 0.5 to 29.8]. One month after CHTC, safe sex was higher among female-positive couples (75%) than among female-negative couples (3%) (RR: 30.0, 95% CI: 4.3 to 207.7). Safe sex increased substantially after CTHC for female-positive couples (RR 9.6, 95% CI: 4.6 to 20.0), but not for female-negative couples (RR: 1.2, 95% CI: 0.1 to 18.7). Conclusions: Engaging pregnant couples in CHTC can have prevention benefits for couples with an HIV-infected pregnant woman, but additional prevention approaches may be needed for couples with an HIV-uninfected pregnant woman. Abstract : Supplemental Digital Content is Available in the Text.